The Abuses of Political Correctness in American Academia: Reading Philip Roth’s The Human Stain in Light of Mary McCarthy’s The Groves of Academe - Petr Anténe (American and British Studies Annual, 2015)
Both Mary McCarthy’s The Groves of Academe (1952) and Philip Roth’s The Human Stain (2000) are campus novels satirizing the political environment of their time. Roth’s novel presents the life story of Coleman Silk, a classics professor at fictional Athena College who is towards the end of his career unjustly charged of using a racial slur against African Americans in the classroom. The case is taken up by his department head and Silk is forced to resign. This more recent indictment of American political correctness provides interesting frames of comparison with McCarthy’s earlier novel. In this text, literature professor Henry Mulcahy, who is to lose his job at the fictional Jocelyn College, spreads the rumor that he is being dismissed because he was once a member of the Communist Party. Mulcahy’s motivation is a belief that the college and faculty are too politically correct to be seen as persecuting the Left. Not only does Mulcahy keep his job, but the college president is forced to resign. While almost half a century apart, both novels provide a harsh satire of American academia, highlighting ways in which the obsession with political correctness can be abused with devastating results. Most revealingly, in the earlier novel the corrupted faculty member abuses the well-intentioned institution, whereas in the more recent text the innocent individual is victimized.